State-of-the-art imaging of liver fibrosis and cirrhosis: A comprehensive review of current applications and future perspectives - Adrian Huber; Lukas Ebner; Johannes T. Heverhagen; Andreas Christe (European Journal of Radiology Open, 2015)
Objective: The purpose of this article is to provide a comprehensive overview of imaging findings in patients with hepatic fibrosis and cirrhosis; and to describe which radiological/clinical modality is best for staging hepatic fibrosis. Conclusion: MR elastography (MRE) appears to be the most reliable method for grading liver fibrosis, although the CT fibrosis score derived from the combination of caudate-to-right-lobe ratio and the diameters of the liver veins significantly correlates with the stage of fibrosis.